The effects of sedation with propofol and propofol- ketamin combination on postoperative cognitive function in elderly patients undergoing spinal anesthesia - Colak, Yusuf Ziya; Ozgul, Ulku; Aslan, Duygu Demiroz; Cumurcu, Hatice Birgul; Colak, Cemil; Durmus, Mahmut (Annals of Medical Research, 2021)
Aim: Elderly patients frequently require surgery. Postoperative cognitive dysfunction (POCD) is an adverse event and reduces thepatient’s quality of life. We aimed to compare the effects of sedation applied with propofol or propofol-ketamine (ketofol) combinationon hemodynamics and POCD during spinal anesthesia in elderly patients undergoing urological surgery.Materials and Methods: Study was performed on 60 ASA I-III patients over 65 years of age. Before the operation (standardizedMini Mental Test) sMMT was applied by a blind researcher. The cases were randomly divided into two groups as propofol (Group P,n=30) and ketofol (Group K, n=30). ECG, SpO 2 , Bispectral Index (BIS), noninvasive blood pressure (NIBP) was monitored. After spinalanesthesia, group P received propofol 0.5 mg/kg IV bolus and then 1.5 mg/kg/hour infusion. Group K received propofol 0.4 mg/kg and ketamine 0.1 mg/kg IV bolus and then propofol 1.2 mg/kg/hour and ketamine 0.3 mg/kg/hour infusion. Hemodynamic andrespiratory data were recorded. The sedation level was monitored by RAMSAY sedation score. sMMT was repeated by the researcherwho performed the initial test at postoperative first 24 hours and postoperative 3rd day.Results: Significant decreases were observed for heart rate, SAP, and MAP in both groups compared with baseline values. Nostatistically significant difference was detected between the groups in sMMT values at postoperative 1 st and 3 rd days. Within-group comparisons revealed significant differences between preoperative sMMT and postoperative 1 st day sMMT and betweenpostoperative 1 st and postoperative 3 rd day sMMT (p< 0.001). No difference was detected between preoperative and postoperative3 rd day sMMT (p< 0.25). In Group P, there was statistically significantly higher injection pain (p
Keywords: Cognitive dysfunction; elderly patient; ketamine; propofol; spinal anesthesia